The Triassic Marine Biota of Eastern Indonesia and its Interregional and Global Correlation: A Review - Hasibuan, Fauzie (Geological Agency, 2010)
DOI:Â 10.17014/ijog.v5i1.91The interregional and global correlation of the Triassic biota of Indonesia was based on the review of previous workers and the author himself. Scythian Epoch (Early Triassic) in Timor is subdivided into Early Scythian with Ophiceras demisso, Meekoceras sp., Pseudomonotis subaurita, Gervillia subpannonica, and Myophoria sp., whilst Late Scythian is indicated by the presence of Owenites egrediens and Sibirites sp. The presence of Anisian Stage (Middle Triassic) in Misool is indicated by ammonite Beyrichites and bivalve Daonella lilintana. In Timor, this stage is pointed out by the presence of Joannites cymbiformis, Monophyllites wengensis, Protrachyceras archaelus, Daonella indica, Tracyceras cf. aon, Brochidium timorense, and Lima subpunctatoides. Terebellina mackayi found above Beyrichites-bearing bed in Misool has an age range from Anisian to Ladinian. It is concluded that the boundary between Anisian and Ladinian lies between beds with Beyrichites and Terebellina mackayi. Early Carnian Stage (Late Triassic) in Timor is indicated by the presence of Joanites cymbiformis, Waldhausenites sp., Miltites sp., and Halogyra cipitiensis; whereas Late Carnian is indicated by the presence of Cladicites crassestriatus and Tropites subbulatus. The presence of Halobia verbeeki, Pinacoceras parma, Neobetites sp., Parabetites sp., Malayites sp., Amarassites sp., and Halorites sp., indicates the Early Norian Stage, whilst the presence of Cladiscites tornatus, Cyrtopleurits malayicus, and Trachypleuraspidites sp. implies the Late Norian. The Rhaetian Stage in Timor contains Choristoceras indoaustralicum, whereas in Misool it contains Choristoceras sp. and Cochloceras sp.